miR-129-5p Regulates the Immunomodulatory Functions of Adipose-Derived Stem Cells via Targeting Stat1 Signaling - He-Yang Zhang; Yu-Han Wang; Yan Wang; Yan-Nv Qu; Xiao-Hui Huang; Hui-Xin Yang; Chang-Ming Zhao; Youdi He; Si-Wei Li; Jin Zhou; Changyong Wang; Xiao-Xia Jiang (Hindawi Limited, 2019)
Adipose-derived stem cells (ASCs) have become one of the most promising stem cell populations for cell-based therapies in regenerative medicine and for autoimmune disorders owing to their multilineage differentiation and immunomodulatory capacities, respectively. One advantage of ASC-based therapy lies in their immunosuppressive potential. However, how to get ASCs to provide consistent immunosuppression remains unclear. In the current study, we found that miR-129-5p was induced in ASCs treated with inflammatory factors. ASCs with miR-129-5p knockdown exhibited enhanced immunosuppressive capacity, as evidenced by reduced expression of proinflammatory factors, with concurrent increased expression of inducible nitric oxide synthases (iNOS) and nitric oxide (NO) production. These cells also had an increased capacity to inhibit T cell proliferation in vitro. ASCs with miR-129-5p knockdown alleviated inflammatory bowel diseases and promoted tumor growth in vivo. Consistently, ASCs that overexpressed miR-129-5p exhibited reduced iNOS expression. Furthermore, we show that miR-129-5p knockdown in ASCs results in hyperphosphorylation of signal transducer and activator of transcription 1 (Stat1). When fludarabine, an inhibitor of Stat1 activation, was added to ASCs with miR-129-5p knockdown, iNOS mRNA and protein levels were significantly reduced. Collectively, these results reveal a new role for miR-129-5p in regulating the immunomodulatory activities of ASCs by targeting Stat1 activation. These novel insights into the mechanisms of ASC immunoregulation may lead to the consistent production of ASCs with strong immunosuppressive functions and thus better clinical utility of these cells.